Alfisol Soil Fertility Before Planting and After Harvest as Meloon Planting Media with Bioboost Fertilization - Nurul Fajeriana; Muzna Ardin Abdul Gafur (Jurnal Penelitian Pertanian Terapan, 2023)
Soil fertility is the potential of the soil to provide nutrients in sufficient quantities in available and balanced forms to ensure optimum plant growth and production. The current availability of nutrients in the soil has decreased due to continuous land use with the use of chemical fertilizers in the cultivation process, plus leaching and erosion by rainwater, not least in Alfisol soils. Therefore, fertilization with organic materials is carried out, namely the provision of Bioboost fertilizer. Bio boost is a biological fertilizer containing superior soil microorganisms, helpful in increasing soil fertility as a result of soil biochemical processes. One of the applications of organic cultivation is the cultivation of melon (Cucumis melo L.) because melon is a plant with high economic value and is profitable to be cultivated as a source of income for farmers. Based on this, a study was conducted to determine the nutrient status of Alfisol soil before planting and after harvesting which was used as a Melon plant with various concentrations of Bioobost fertilization. Furthermore, for the analysis of soil fertility, laboratory analysis was carried out by taking 1 kg of disturbed soil samples that had been air-dried and then analyzing soil properties, namely texture, pH (H2O), C-Organic (%), Nitrogen (%), P2O5 (ppm), K (cmol kg-1), Ca (cmol kg-1), Mg (cmol kg-1), Na (cmol kg-1), Na (cmol kg-1), CEC (cmol kg-1), and base saturation (%). The application of Bio boosts fertilizer showed an increase in the nutrient status of Alfisol soil as a Melon growing from low to moderate categories before planting to medium to high categories after harvest. The more concentration of Bioboost fertilizer given, the soil nutrient status also increases. The concentration of P4 (1100ml bio boost + 400ml water) gave the highest increase in nutrient status. Keywords: Agrotechnology; organic-fertilizer; soil-chemical